Несколько интерпретационных стереотипов в свете стратиграфических и иных наблюдений на Нетайловском могильнике - Жиронкина, О.Ю.; Цитковская, Ю.И. (My University, 2004)
O. Zhironkina, Yu. Tsitkovskaya. Some Interpretational Stereotypes in the Light of Stratigraphic and Other Observations at Netaylavsky Burial Ground Priority of mnemologic part of posthumous treatment (funeral repast, attendance at grave, construction of monuments, etc.) over the ptomatological procedure (actions taken with the corpse), especially typical for the modern society, seems to have influenced the popularity of RND hypothesis (the rite of neutralization of the dead) to a great extent. Being a logical explanation of the poor state of preservation and anatomical disorder of bone remains in the Early Mediaeval burial places, this does not contradict with common contemporary stereotypes, yet might not totally conform with ideas of the Early Medieval people.